Austerity, personalization and the degradation of voluntary sector employment conditions. (June 2015) - Cunningham, Ian
This qualitative study of two social care organizations, explores how public sector austerity and policies to personalize social care services through introducing individual budgets in the UK combine to reshape employment conditions. It further explores how these new market relations impact on staff morale and commitment. The individual case summaries reveal a remarkable degree of similarity in terms of employment outcomes, with social care workers experiencing an erosion of the standard employment relationship. Workers experience greater insecurity in areas of pay and conditions, working time, training and development, career prospects, along with work intensification. Worker morale appeared vulnerable as employees struggled to cope with worsening working conditions, but also expressed concerns with quality of care in an era of austerity.